2018
DOI: 10.1016/j.jallcom.2018.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zr and Al addition on nanocluster formation in oxide dispersion strengthened steel - An ab initio study

Abstract: Conventional Oxide dispersion strengthened steels are characterized by thermally stable, high density of Y-Ti-O nanoclusters, which are responsible for their high creep strength. Ti plays a major role in obtaining a high density of ultrafine particles of optimum size range of 2-10 nm. In Al-containing ODS steels developed for corrosion resistance, Y-Al-O clusters formed are of size range 20 -100 nm, and Ti fails in making dispersions finer in the presence of Al. Usage of similar alloying elements like Zr in pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 33 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…Some research works 18,25 indicated that compared with Ti and Al, Zr is more likely to react with Y, O, and form Y‐Zr‐O particles, typically Y 4 Zr 3 O 12 phase 26 . This result also agrees with the phase calculation by Mohan 27 . The size of Y 4 Zr 3 O 12 particles is usually similar to that of Y‐Ti‐O particles, which is much finer than Y‐Al‐O particles 11,26 .…”
Section: Introductionsupporting
confidence: 78%
“…Some research works 18,25 indicated that compared with Ti and Al, Zr is more likely to react with Y, O, and form Y‐Zr‐O particles, typically Y 4 Zr 3 O 12 phase 26 . This result also agrees with the phase calculation by Mohan 27 . The size of Y 4 Zr 3 O 12 particles is usually similar to that of Y‐Ti‐O particles, which is much finer than Y‐Al‐O particles 11,26 .…”
Section: Introductionsupporting
confidence: 78%
“…This explicit precipitatematrix correlation in atomic scale is a conclusive evidence to the fact that the Y 2 O 3 is dissolving during the milling and it is re-precipitating as Y-Zr-O nuclei during hot-consolidation in an energetically preferred manner. The low formation energy favours Y 4 Zr 3 O 12 than other structures in Y-Zr-O system [28,37]. Existence of a few random orientations with high order zone axes might be due to:(i) loss of coherency in the growth phase as the strain energy overweighs the interfacial energy [30] or (ii) they nucleate with various orientation relationships owing to the non-equilibrium nature of the ball milling process [38].…”
mentioning
confidence: 99%
“…The Ti addition was expected to react with Y and O to form Y-Ti-O oxides within alloys (Y 2 Ti 2 O 7 , Y 2 TiO 5 ) [ 15 ]. The addition of Al in the ODS steel was not only expected to form Y-Al-O oxides [ 16 , 17 , 18 , 19 , 20 ] but also to improve the corrosion resistance by forming dense Al 2 O 3 scales on the surface of the alloy, which limited further corrosion of the matrix under the oxide layer. In addition, the presence of Al can suppress embrittlement at 475 °C by suppressing the phase separation of the ferritic phase into the two phases, Fe-rich ferrite and Cr-rich ferrite in high Cr steel [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%